PENGARUH PAKAN DARI AMPAS TAHU YANG DIFERMENTASI DENGAN EM4 TERHADAP PERTUMBUHAN IKAN PATIN (Pangasius sutchi) - Sartika, Lesa; Nurhadi, Nurhadi; Abizar, Abizar (STKIP PGRI Sumbar, 2013)
ABSTRACT At the present time are rarely people who breed fish one Catfish. Because except of limited land prices also feed expensive. Then to overcome this expensive feed prices is need for alternative feed. Alternative this can be done by creating artificial feed. Feed can be derived from the fermented tofu waste with EM4. Based on this research has been conducted aimed to determine the effect of feeding fermented tofu waste with EM4 on the growth of Catfish (Pangasius sutchi). This experiment was set in a Completely Randomized Design (CRD) with four treatments and six replicates. Treatment were diets with: A. Control (By giving feed FF999), B. By giving tofu waste was done fermentation 10%, C. By giving tofu waste was done fermentation 16%, and D. By giving tofu waste was done fermentation 24%. Results of experiment indicated that of fermented tofu waste levels in the feed showed a 10% in crease in total body weight and lenght catfish tend to use better than other treatments. But for feed conversion showed similar results in each treatments.